The Potential of Cireundeu Traditional Culture (Rasi) in Education for Sustainable Development (ESD) in Biology Learning - Fadilah, Solikhah Isti; Umar, Mohammad Farhan; Riandi, Riandi; Solihat, Rini; Sriyati, Siti (Jurnal Pendidikan Biologi, 2024)
Indonesia is an agricultural country that still imports large amounts of rice. The increasing number of rice imports in Indonesia in recent years may indicate that food security in Indonesia is still low. This problem can be raised in learning that is integrated with Education for Sustainable Development (ESD). The aim of ESD is to equip students with the skills necessary to reflect on their behavior and consider the social, cultural, economic, and environmental impacts of their activities, from both a local and global perspective. ESD learning can also be supported by indigenous phenomena such as Rasi. Rasi is one of Cireundeu's traditional cultures, which has a sustainable food management system. Food security issues integrated with Rasi can be used as an effort to achieve Sustainable Development Goals (SDGs) target point two, namely ending hunger to achieve food security, improving nutrition, and encouraging sustainable agriculture. This ESD-integrated learning can be applied to biology learning in the independent curriculum phase F, especially in the digestive system chapter, sub-chapter food content.